The influence of three-dimensional structure on naïve T cell homeostasis and aging - Lambert, Simon; Cao, Wenqiang; Zhang, Huimin; Colville, Alex; Liu, Jie-Yu; Weyand, Cornelia M.; Goronzy, Jorg J.; Gustafson, Claire E. (Frontiers in Aging, 2022)
A breakdown in cellular homeostasis is thought to drive naïve T cell aging, however the link between naïve T cell homeostasis and aging in humans is poorly understood. To better address this, we developed a lymphoid organoid system that maintains resting naïve T cells for more than two weeks, in conjunction with high CD45RA expression. Deep phenotypic characterization of naïve T cells across age identified reduced CD45RA density as a hallmark of aging. A conversion from CD45RAhigh naive cells to a CD45RAlow phenotype was reproduced within our organoid system by structural breakdown, but not by stromal cell aging or reduced lymphocyte density, and mediated by alternative CD45 splicing. Together, these data suggest that external influences within the lymph node microenvironment may cause phenotypic conversion of naïve T cells in older adults.